Indigenous Societies in Santiago del Estero: Preliminary Notes from Archeology and History. Late Prehispanic and Early Colonial Periods - Farberman, Judith (2012)
This article aims to provide an interpretation of 16th Century colonial chronicles of Santiago del Estero Province based on the queries and results of archaeological research. It refers specifically to the so-called “Diaguita”, “Tonocoté”, “Lule” and “Jurí” groups, focusing on the inconsistencies emerging from the confrontation between diverse textual sources and material evidence such as the weak archeological traces from the “Diaguita culture” in Santiago del Estero.